Impact of COVID-19 pandemic response on uptake of routine immunizations in Sindh, Pakistan: An analysis of provincial electronic immunization registry data. Issue 45 (21st October 2020) - Chandir, Subhash; Siddiqi, Danya Arif; Mehmood, Mariam; Setayesh, Hamidreza; Siddique, Muhammad; Mirza, Amna; Soundardjee, Riswana; Dharma, Vijay Kumar; Shah, Mubarak Taighoon; Abdullah, Sara; Akhter, Mohammed Adil; Ali Khan, Anokhi; et al.
Highlights: One out of two children missed routine immunizations during COVID-19 lockdown in Sindh. COVID-19 lockdown disproportionately affected coverage rates across the districts. Drop in the number of immunizations was higher in rural areas followed by urban slums. Expanding pool of un-immunized children is bringing down herd immunity and raising the risk of vaccine-preventable disease outbreaks. Abstract: Background: COVID-19 pandemic has affected routine immunization globally. Impact will likely be higher in low and middle-income countries with limited healthcare resources and fragile health systems. We quantified the impact, spatial heterogeneity, and determinants for childhood immunizations of 48 million population affected in the Sindh province of Pakistan. Methods: We extracted individual immunization records from real-time provincial Electronic Immunization Registry from September 23, 2019, to July 11, 2020. Comparing baseline (6 months preceding the lockdown) and the COVID-19 lockdown period, we analyzed the impact on daily immunization coverage rate for each antigen by geographical area. We used multivariable logistic regression to explore the predictors associated with immunizations during the lockdown. Results: There was a 52.5% decline in the daily average total number of vaccinations administered during lockdown compared to baseline. The highest decline was seen for Bacille Calmette Guérin (BCG) (40.6% (958/2360) immunization at fixed sites. Around 8438 children/day were missing immunization during the lockdown. Enrollments declined furthest in rural districts, urban sub-districts with large slums, and polio-endemic super high-risk sub-districts. Pentavalent-3 (penta-3) immunization rates were higher in infants born in hospitals (RR: 1.09; 95% CI: 1.04–1.15) and those with mothers having higher education (RR: 1.19–1.50; 95% CI: 1.13–1.65). Likelihood of penta-3 immunization was reduced by 5% for each week of delayed enrollment into the immunization program. Conclusion: One out of every two children in Sindh province has missed their routine vaccinations during the provincial COVID-19 lockdown. The pool of un-immunized children is expanding during lockdown, leaving them susceptible to vaccine-preventable diseases. There is a need for tailored interventions to promote immunization visits and safe service delivery. Higher maternal education, facility-based births, and early enrollment into the immunization program continue to show a positive association with immunization uptake, even during a challenging lockdown.